Use of sonic waves in bubble formation, microhardness and fluoride release of a high-viscosity glass-ionomer cement - Lima Hironaka, Nallu Gomes; Trizzi, Juliana Quintino [UNESP]; Yoshida, Natalia Miwa; Cury, Jaime Aparecido; Machado Tabchoury, Cinthia Pereira; Botelho, Juliana Nunes; Pini, Nubia Inocencya Pavesi; Pascotto, Renata Correa (Wiley-Blackwell, 2019)
Aim High-viscosity glass-ionomer cements (HV-GIC) are indicated for restorations but their viscosity favors the inclusion of bubbles within it. This study aimed to evaluate the use of ultrasonic and sonic waves in bubble formation, microhardness and fluoride release in a HV-GIC, also considering a different powder:liquid ratio (P/L). Methods Twenty-four molars with occlusal cavities were divided into four groups (N = 6): CG, HV-GIC with manual insertion; UG, application of ultrasonic waves; SG, application of sonic waves; and FG, HV-GIC fluid (1:2 P/L) with manual insertion. After 24 hours, bubbles and microhardness (50 g/5 s) were measured. Fluoride release (N = 10) was evaluated in CG, SG and UG after cariogenic challenge for 11 days. Microhardness, total area and number of bubbles, and fluoride release were submitted to ANOVA and Tukey's test. The average size of bubbles was analyzed by Kruskal-Wallis test (alpha = 5%). Results FG presented the lowest value of microhardness and higher average size for bubbles (P < .05). Differences concerning total number, total area occupied by bubbles and fluoride release were not found (P > .05). Conclusion The use of sonic and ultrasonic waves had no influence on bubble formation, microhardness and fluoride release of a HV-GIC. Changing the P/L is not recommended.
Keywords: fluorides; glass-ionomer cement; microhardness